Quality Evaluation of Onion Slices Dried Using Low Pressure Superheated Steam and Vacuum Drying - Sehrawat, Rachna; Nema, Prabhat K.; Chandra, Pitam (Journal of Agricultural Engineering, 2018)
The effect of combined low pressure superheated steam drying (LPSSD) followed by vacuum drying (VD) on quality of onion slices at different temperature (60-80 oC 10 kPa) was determined. In the first stage, the moisture content of onion slices was reduced to 50 % (w.b.) from 88-90 % (w.b.) using LPSSD; and then it was further reduced up to 7-8 % (w.b.) by VD. It was found that among the various drying temperatures studied, retention of colour, rehydration ratio, thio-sulphinate content and antioxidant capacity of dehydrated onion was better at 60 oC, followed by 70 oC, whereas total phenol contents were higher at 80 oC. The results of control dried sample and sample dried at 60 oC had significant differences in time taken for drying, thio-sulfinate content, total phenol content and antioxidant capacity, whereas insignificant effects of drying temperature was observed on rehydration and water activity of dried onion slices.